Sustainable HRM practices for a stronger employer brand: Leveraging organizational culture - Aydan Huseynova; Jana Matošková (Scientific Papers of the University of Pardubice, Series D: Faculty of Economics and Administration, 2022)
The business of the current era intends to show competitive advantage for a long run in order to get more profits and stay alive in the markets. Getting a competitive advantage is highly related to human resource management (HRM). Companies build a distinct employer brand based on their competitive advantage; however, the role of organizational culture to support the transition of companies to get a powerful employer brand is rarely studied. Consequently, the main purpose of the current study is to determine the mediating role of organizational culture (engagement and productivity) in the relationship between sustainable HRM practices and employer branding. The survey research design was used and data were collected from 420 employees of Azerbaijani organizations using a convenience sample strategy. The findings of the path analysis using AMOS revealed the partial multiple mediating role of organizational culture (engagement and productivity) in the relationship between sustainable HRM practices and employer branding. Moreover, as far as the individual mediating role is concerned, the mediating role of organizational engagement is stronger compared to productivity. The findings highlighted that by implementing Sustainable HRM practices and maintaining an engaged organizational culture in the employer brand, employers can meet their employees' various requirements and expectations while maintaining a consistent company image.
Keywords: M; M12; 330; Human resource management; Organizational culture; Employer branding; Sustainable HRM; Person-organization fit theory